Prognostic impact of uric acid levels in heart failure with mildly reduced ejection fraction: insights from a large retrospective registry - Schmitt, Alexander; Behnes, Michael; Bertsch, Thomas; Reinhardt, Marielen; Görtz, Michelle; Abel, Noah; Lau, Felix; Weidner, Kathrin; Dudda, Jonas; Steffen, Henning Johann; Abumayyaleh, Mohammad S. A.; Dürschmied, Daniel; et al. (European journal of internal medicine, 2025)
Background - Elevated uric acid (UA) is a recognized biomarker in patients with cardiovascular disease. However, the prognostic significance of UA levels in patients with heart failure (HF), particularly those with HF with mildly reduced ejection fraction (HFmrEF), remains unexplored. - Methods - From 2016 to 2022, consecutive patients hospitalized with HFmrEF at one medical centre were retrospectively included. Patients were stratified by pre-specified UA levels (i.e., normal UA: ≥3.5 - ≤6.0 (females) or ≤7.0 (males); low UA: <3.5 and high UA: >6.0 (females) or >7.0 mg/dL (males)), further stratification was performed by UA quintiles. The primary endpoint was all-cause mortality at 30 months (median follow-up), the key secondary endpoint was HF-related rehospitalization. - Results - The study cohort comprised 1419 HFmrEF patients with a median UA of 6.0mg/dL. UA levels above (H) and below (L) the normal range (N) were predictive for the risk of all-cause mortality at 30 months (H: 42% and L: 43% vs. N: 27%), which persisted after multivariable adjustments (H vs N: HR=1.230; 95% CI 1.003-1.508; p = 0.046; L vs N: HR=1.915; 95% CI 1.383-2.650; p = 0.001). Furthermore, there was a trend towards a higher risk of long-term HF-related rehospitalization in patients with elevated UA levels (H: 20% vs. N: 9% vs. L: 8%). However, this finding failed to reach statistical significance after multivariable adjustment (H vs. N: HR=1.408; 95% CI 0.995-1.992; p = 0.053). - Conclusion - Both elevated and low UA levels were associated with an increased risk of long-term all-cause mortality in patients with HFmrEF.
Online verfügbar: 8. Juli 2025, Artikelversion: 1. Oktober 2025
Gesehen am 16.12.2025